OCT Angiography and En Face OCT Reflectance Aid in Monitoring Subclinical Inflammation in Serpiginous Choroidopathy - Carl S. Wilkins; Jorge S. Andrade Romo; Toco Y. P. Chui; Richard B. Rosen; Stephanie Llop (Case Reports in Ophthalmological Medicine)
Introduction. We present a case of serpiginous choroidopathy (SC) with novel OCTA and en face OCT reflectance findings which help identify subclinical disease progression. Case Presentation. En face OCT reflectance images demonstrated outer retinal tubules (ORT) at the serpiginous lesion margins of affected and unaffected retina on multimodal imaging. OCTA findings demonstrate variable dropout of choriocapillaris in “normal” retina beyond lesion borders which was not visible on standard imaging and which demonstrated a clear transition zone beyond the ORT. Discussion. This is the first report of choriocapillaris atrophy identified on OCTA not identified on traditional multimodal imaging in serpiginous choroidopathy. Damage to vasculature only visible with OCTA may help characterize the distribution of inflammation, aiding in monitoring of suppression not illustrated by traditional imaging and which may threaten the central macula. ORT in SC suggest death and reorganization of outer segments from dysfunction of the choriocapillaris and RPE, as well as serve to demarcate the area of chronic or old inflammation, supporting the hypothesis that the choriocapillaris is the primary site of inflammation in SC. Based on these findings, we recommend OCTA on all patients with serpiginous choroidopathy to monitor underlying state of inflammation and help determine immunosuppressive threshold.